Influence SIA, SPI, and Budget Targets the Quality Financial Reports PT. Mappadeceng Jaya Lestari - Ar, Andi; M, Nurwani (AJAR, 2024)
This study aims to analyze the partial and simultaneous influence between accounting information systems, internal control systems, and budget targets on the quality of financial reports PT. Mappadeceng Jaya Lestari Parepare City to determine and analyze which variables have the most influence or dominant on the quality of financial reports PT. Mappadeceng Jaya Lestari Parepare City, This study uses quantitative data and the data sources used are primary data and secondary data. The analysis method used is multiple regression analysis, t-test, f-test, correlation coefficient (r) and coefficient of determination (r2). The results showed that the accounting information system and budget goals partially had a positive and significant effect on the quality of financial statements PT. Mappadeceng Jaya Lestari Parepare City, while the internal control system partially did not have a positive and significant effect on the quality of financial statements PT. Mappadeceng Jaya Lestari Parepare City, but simultaneously or together had a positive and significant effect on the quality of financial statements PT. Mappadeceng Jaya Lestari Parepare City and the accounting information system variable is the most influential or dominant variable on the quality of financial statements PT. Mappadeceng Jaya Lestari Parepare City.